Modification of liquid silicone rubber by octavinyl‐polyhedral oligosilsesquioxanes. Issue 36 (2nd June 2016) - Bai, Hongqiang; Huang, Chi; Jun, Liao; Li, Houbin
ABSTRACT: To develop an efficient, simple, and biocompatible method for improving the thermal and mechanical properties of an addition‐type liquid silicone rubber (LSR), octavinyl‐polyhedral oligosilsesquioxane (OPOSS) modified LSR samples were prepared through the addition of 0.5–4.0 wt % OPOSS as a modifier to a platinum‐based silicone curing system before vulcanization. The characterization and measurement of the OPOSS and LSR samples were carried out by Fourier transform infrared spectroscopy, X‐ray diffraction, NMR, gas chromatography/mass spectrometry (electron impact ionization), scanning electron microscopy, thermogravimetric analysis/differential scanning calorimetry, and universal testing. The experimental results show that the crosslinking of the OPOSS and LSR polymer had a significantly positive effect on the thermal and mechanical properties. Compared with the unmodified sample, its tensile strength was enhanced by 423–508%, its tear resistance was increased from 22 to 44%, the residue at 600 °C was increased by 36–75% in an N2 atmosphere and 8–65% in an air atmosphere, respectively. These results were obviously superior to those from other similar reported methods that used larger molecular or nonreactive polyhedral oligosilsesquioxane (POSS) derivatives as modifiers at similar POSS loadings. Furthermore, a significant correlation was found between the loading rate of OPOSS and the thermal properties. However, the mechanical properties seemed negatively correlated with the OPOSS content within the experimental range; this may have been due to a material defect caused by the uneven distribution and agglomeration. The results of this study proved that the incorporation of OPOSS into an LSR polymer matrix by a hydrosilylation reaction could be an efficient way to improve the mechanical properties, thermal stability, and biocompatibility of LSR in the future. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43906. Abstract :